META STRUCTURE OPTIMIZATION OF LI-ON 21700 BATTERY PROTECTION FOR THE APPLICATION OF ELECTRIC VEHICLES - Rafi Fajarsyah Nurhani, Ahmad
One of the key factors that is considered in electric vehicles is battery safety. Electric vehicles battery comprised of an array of 21700 battery is located on the bottom panel of the car which is susceptible to ground impact. In this research sandwich panel with a meta structure core which is known for its high specific energy absorption (SEA). The optimization of meta structure is achieved by varying the geometry, material, height, width, thickness, and stack with quasi-static loading. The meta structure geometry is twisted octet lattice, double arrowhead, and multi stable beam. From literature study it is found that these three geometries have the potential to have a high specific energy absorption (SEA). The research uses a non-linear finite element method to simulate ground impact and design variation is optimized using design for six sigma (DFSS) Taguchi method with L18 orthogonal array and parameter is analyze using analysis of variance. The optimize configuration of the meta structure are double arrow auxetic, material AlSi-12, height and width cell 10 mm, thickness 1.2 mm, and stack number 3. The optimized model has a gain of 9.9 dB with the thickness and width giving the highest effect on the maximum SEA. The optimum configuration is used as the core of a sandwich panel and protects the 21700 battery that it has a maximum deformation of 1.7 mm which is below the failure condition of cylinder battery.